Planting the green idea : a study of medium effectiveness on behavioural intentions using the theory of planned behaviour - Low, Jin Yong (2011)
The Theory of Planned Behaviour (TPB) proposed by Ajzen has traditionally been used by researchers to predict behaviour, explain behavioural changes and to design behaviour interventions to elicit changes. This study seeks to apply TPB to the much neglected research area of "green" behaviour in the context of Singapore.